Microbial and Antimicrobial Susceptibility Profile of Pediatric Hematological Malignancy Patients at a Tertiary Hospital - Adrizain, Riyadi; Sugianli, Adhi Kristianto; Kasih Pasaribu, Elisabeth Putri; Trie Utami, Fadila Dyah; Kwarteng, Alexander (Faculty of Medicine, Universitas Padjadjaran, 2025)
Neutropenia is a major predisposing factor for infection in pediatric patients with hematological malignancies. In Indonesia, data on microbial patterns and antibiotic resistance in this group remain limited, highlighting the need for local data to guide empirical therapy. This study aimed to determine the microbial and antibiotic susceptibility profile of pediatric patients with hematological malignancies. A cross-sectional descriptive study was conducted in the pediatric ward of Dr. Hasan Sadikin General Hospital, Bandung, from April to June 2024. Data were collected retrospectively using total sampling from medical records and registers of patients diagnosed with hematological malignancies (subgroups I and II) between January 2021 and December 2022. Microbial identification and antibiotic susceptibility profiles were performed using an automated colorimetry method. A total of 33 bacterial isolates were identified, with Gram-negative bacteria being the most frequent (75.8%). The predominant isolates were Escherichia coli (39.4%), Klebsiella pneumoniae (15.15%), and Staphylococcus hominis (12.1%). From all isolates, 69.7% were multidrug-resistant organisms (MDROs). About 62.5% of Gram-positive bacteria were methicillin-resistant coagulase-negative Staphylococci (MRCoNS), while 48% and 24% of Gram-negative bacteria were extended-spectrum β-lactamase (ESBL) and carbapenem-resistant, respectively. Gram-positive bacteria showed 100% sensitivity to Linezolid, Tigecycline, and Vancomycin, while Gram-negative bacteria showed the highest sensitivity to Amikacin. Escherichia coli, as the most frequent isolate, showed 100% sensitivity to Tigecycline. In conclusion, Gram-negative bacteria were the predominant organisms, with Escherichia coli being the most common isolate. The antibiotic susceptibility test showed a high proportion of MDROs and decreased susceptibility levels in 2022 compared to 2021.